Real Exchange Rate and Foreign Direct Investment in Sub-Saharan Africa. Some Empirical Results - Oluremi Ogun; Festus O. Egwaikhide; Eric K. Ogunleye (Centro de Investigación y Docencia Económicas, A.C., 2012)
Despite the well acknowledged importance of foreign direct investment (fdi) and efforts of sub-Sahara African (ssa) countries at attracting it, the region remains the least destination for fdi globally. Of course, several studies have endeavored to examine the determinants of fdi in this region. This study contributes to the literature by examining a possible determinant of fdi that has received less attention in the literature: real exchange rate (rer) movements. This paper examines this relationship with a view to determining the extent to which real exchange rate movements stifle fdi inflows in selected ssa countries, employing the Granger causality and simultaneous estimation techniques. The use of simultaneous equation is informed by the theoretical and empirical inconclusiveness on the relationship between movements in rer and fdi. The Granger Causality test further provides insight on the causal direction of the variables. Whereas the causality tests suggest statistical dependence between rer movements and fdi for a few of the countries, the regression analyses show a statistically significant relationship between these variables. While the inclusion of pre-reform period in the study may have contributed to these results, the general picture emerging is that fdi flows are sensitive to reer movements in ssa.